A new design of a lentiviral shRNA vector with inducible co-expression of ARGONAUTE 2 for enhancing gene silencing efficiency. Issue 1 (December 2015) - He, Jiening; Huang, Lian; Qiu, Huiling; Li, Jiexuan; Luo, Lan; Li, Yanjiao; Tian, Shengli; Kang, Kang; Luo, Jun; Liu, Lin; Gou, Deming
Abstract Background RNA interference (RNAi) is a robust tool for inhibiting specific gene expression, but it is limited by the uncertain efficiency of siRNA or shRNA constructs. It has been shown that the overexpression of ARGONAUTE 2 (AGO2) protein increases silencing efficiency. However, the key elements required for AGO2-mediated enhancement of gene silencing in lentiviral vector has not been well studied. Results To explore the application of AGO2-based shRNA system in mammalian cells, we designed shRNA vectors targeting the EGFP reporter gene and evaluated the effects of various factors on silencing efficiency including stem length, loop sequence, antisense location as well as the ratio between AGO2 and shRNA. We found that 19 21-bp stem and 6- or 9-nt loop structure in the sense-loop-antisense (S-L-AS) orientation was an optimal design in the AGO2-shRNA system. Then, we constructed a single lentiviral vector co-expressing shRNA and AGO2 and demonstrated that the simultaneous expression of shRNA and AGO2 can achieve robust silencing of exogenous DsRed2 and endogenous ID1 and P65 genes. However, the titers of packaged lentivirus from constitutive expression of AGO2 vector were extremely low, severely limiting its broad application. For the first time, we demonstrated that the problem can be significantly improved by using the inducible expression of AGO2 lentiviral system. Conclusions We reported a novel lentiviral vector with an optimal design of shRNA and inducible AGO2 overexpression which provides a new tool for RNAi research.